Analysis On Shift In English - Indonesian Subtitling Of Freedom Writers Film - Hati, Pratiwi Indah Permata; , M.Hum Dr. Dwi Haryanti (2017)
This research studies the translation shift of the utterance in English-Indonesian translation of Freedom Writers film. The objectives of the study are to identify the translation shift that found in Freedom Writers film and to describe the quality of translation in it. This research is descriptive qualitative research. The data are utterances or sentences contains of shifts in Freedom Writers film. The data source is Freedom Writers film by paramount production. The data are analyzed by describing method using Catford's and Nababan's theory.The result of the study shows that, there are four translation shifts that found in Freedom Writers film, namely: class shift, intra system shift, unit shift and structure shift. From 893 data the researcher finds 22 utterances or 2,46% belongs to class shift, 178 utterance or 19,93% belongs to intra system shift, 312 utterance or 34,94% belongs to unit shift and 381 utterance or 42,67% belongs to structure shift. The dominant shift in this research is structure shift which get 42,67% from 100%. Secondly, the translation quality divided into accuracy, acceptability, and readability level. Freedom Writers film has 1466 utterance or 99,32% belongs to accurate translation, 10 utterance or 0,68% belongs to less accurate translation, and none data belongs to inaccurate, they are in accuracy level. In acceptability level 1367 utterance or 92,61% belongs to acceptable, 107 utterance or 7,25% belongs to less acceptable and 2 utterances or 0,14% belongs to unacceptable utterance in this data. While in readability level, it has 1473 utterance or 99,8% belongs to high readability, 3 utterances or 0,2% belongs to medium readability and there is no low readability utterance in this data. It can be concluded that the translation shift in Freedom Writers film is an accurate, an acceptable, and a readable translation for the reader.Keywords: freedom writers film, translation shifts, translation quality